Simply painting. Watercolors. Vol. 2, The South & Southwest [videorecording (DVD)] - Clarke, Frank, 1938- (Kultur, 2008)
Demonstrates watercolor techniques for rendering landscapes depicting locales in Florida (disc 1) and the Southwest (disc 2).